Camal municipal para la ciudad de Babahoyo y sus áreas de influencia - Kühn Vega, Pablo Ernesto (2012)
The proper treatment of human food guarantees that this provides to the people the quantity and quality needed of nurients to develop in efficient way through their lives. The food is naturally in vegetation and animals providing each one of it vitamins, minerals and also proteins